Pedagogy and ICT Use 2008
DOI: 10.1007/978-1-4020-8928-2_6
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Characteristics, Contextual Factors, and How These Affect the Pedagogical Use of ICT

Abstract: Whether and how teachers use ICT in their teaching and their pedagogical orientations are influenced by personal, organizational, and system-level factors. In accordance with the conceptual framework described in Chapter 2, the teacher questionnaire was designed to collect data on a number of variables related to these three categories of factors. Questions related to the personal characteristics of the teacher included demographic information (age, gender, highest level of academic qualification reached, poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0
20

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 0 publications
5
56
0
20
Order By: Relevance
“…These factors are considered crucial for the success of any technological innovation in teaching and learning (Ng, 2011). A comparative study of pedagogy and ICT use in schools in 22 different countries concluded that teachers' pedagogical and technical competence in the use of technology are significant predictors for technology adoption in teaching practice (Law & Chow, 2008). These two components have been examined through the categories of knowledge, attitudes, skills, and habits (Bonanno, 2011;Eslaminejad, Massood, & Ngah, 2010).…”
Section: Components Of the Teachers' Readinessmentioning
confidence: 99%
“…These factors are considered crucial for the success of any technological innovation in teaching and learning (Ng, 2011). A comparative study of pedagogy and ICT use in schools in 22 different countries concluded that teachers' pedagogical and technical competence in the use of technology are significant predictors for technology adoption in teaching practice (Law & Chow, 2008). These two components have been examined through the categories of knowledge, attitudes, skills, and habits (Bonanno, 2011;Eslaminejad, Massood, & Ngah, 2010).…”
Section: Components Of the Teachers' Readinessmentioning
confidence: 99%
“…However, it is worth noting that other authors (e.g. Law and Chow 2008;Pelgrum 2008) have found advanced training options to focus more on technological aspects rather than on the didactic integration of ICT into relevant scenarios of teaching and learning. The unavailability of relevant options for professional development may thus also play a role here.…”
Section: Introductionmentioning
confidence: 99%
“…A pesar de esta falta de acuerdo, a partir de la revisión de las distintas propuestas se puede distinguir claramente dos ámbitos de competencia: tecnológicas y pedagógicas. Ambos vertebran el conjunto competencial del profesorado (Almerich, Suárez, Orellana y Díaz, 2010;Law and Chow, 2008;Suárez et al, 2010;Suárez-Rodríguez, Almerich, Díaz-García y Fernández-Piqueras, 2012).…”
Section: Introductionunclassified